Investigating high levels of small group participation in churches: case study research from Australia. Issue 4 (3rd July 2020) - Hussey, Ian
ABSTRACT: This paper reports on research into the phenomenon of higher levels of participation in church small groups using a Case Study methodology. Specifically, it studies three Australian churches with high levels of small group participation. The study of these exemplary cases yields information about not only what makes for attractive church small groups but also how congregations can foster high levels of participation. The research identifies the development of a churchwide culture of invitation and hospitality, structures that support high levels of participation and an emphasis on Bible study as the focus of the small group gatherings as crucial factors. These findings counter criticisms of church small groups suggested by some scholars.